1999
DOI: 10.1530/jrf.0.1170369
|View full text |Cite
|
Sign up to set email alerts
|

Growth and cellular proliferation of pig corpora lutea throughout the oestrous cycle

Abstract: Corpora lutea were obtained from gilts on days 2, 4, 8,12,15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…Consistent with the more limited data of Ricke et al [39] on progesterone content and 3␤-HSD protein expression, we observed a rapid increase in progesterone production, progesterone release, and mRNA expression for StAR protein, P450 scc , and 3␤-HSD in HR and RH gilts in the 12-to 24-h period after ovulation. Our observation that progesterone content in luteal tissue was highly correlated with both oviductal and peripheral plasma progesterone concentrations further extends the data of Ricke et al [39] and suggest that because of the activity of the subovarian countercurrent transfer system in pigs [40], oviductal progesterone concentrations will reflect changes in early luteal function and exert regulatory effects on the oviduct [41]. Although Ricke et al [39] indicated that luteal progesterone content provides a good index of normal luteal function, our data suggest that progesterone production and release by luteal tissue in vitro are better measures of luteal status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the more limited data of Ricke et al [39] on progesterone content and 3␤-HSD protein expression, we observed a rapid increase in progesterone production, progesterone release, and mRNA expression for StAR protein, P450 scc , and 3␤-HSD in HR and RH gilts in the 12-to 24-h period after ovulation. Our observation that progesterone content in luteal tissue was highly correlated with both oviductal and peripheral plasma progesterone concentrations further extends the data of Ricke et al [39] and suggest that because of the activity of the subovarian countercurrent transfer system in pigs [40], oviductal progesterone concentrations will reflect changes in early luteal function and exert regulatory effects on the oviduct [41]. Although Ricke et al [39] indicated that luteal progesterone content provides a good index of normal luteal function, our data suggest that progesterone production and release by luteal tissue in vitro are better measures of luteal status.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation that progesterone content in luteal tissue was highly correlated with both oviductal and peripheral plasma progesterone concentrations further extends the data of Ricke et al [39] and suggest that because of the activity of the subovarian countercurrent transfer system in pigs [40], oviductal progesterone concentrations will reflect changes in early luteal function and exert regulatory effects on the oviduct [41]. Although Ricke et al [39] indicated that luteal progesterone content provides a good index of normal luteal function, our data suggest that progesterone production and release by luteal tissue in vitro are better measures of luteal status. For example, progesterone production and release in tissue recovered from the HRϩI group was higher than in HR and RH groups, whereas luteal tissue progesterone content did not differ among the three treatments.…”
Section: Discussionsupporting
confidence: 91%
“…This might be due not only to luteal cells proliferation [39], but also to endothelial cells proliferation (1). Also, in the cow, ewe and sow, DNA content and rate of DNA synthesis increased linearly, from early CL until the mature CL was formed [1,40,41]. The decrease in both microvascular areas and DNA content in Late-CL and regressed luteal structure in the present study suggests that blood vessel regression is associated with tissue involution that occurs during regression of the luteal structures [35,42].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the administration of P 4 antagonist molecule, RU486, significantly decreased VEGF synthesis in vivo , in rat ovary [43] and in monkey endometrium [37]. Even if P 4 influence on ovarian blood flow was demonstrated [44][47], during the periovulatory stage, when the LH surge induces a complete inversion of follicular steroid secretion [8], the role exerted by steroids on follicular VEGF synthesis still remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%